PENGARUH KINERJA LINGKUNGAN, BIAYA LINGKUNGAN DAN OPERATING EFFICIENCY TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2015-2021) - Tessa Okprasari; Ilham Illahi (CV. Adiba Aisha Amira, 2023)
This study aims to determine and analyze the effect of Environmental Performance, Environmental Costs and Operating Efficiency on the Performance of Mining Companies listed on the Indonesia Stock Exchange in 2015-2021. This research is included in quantitative research. The population of this study is mining companies listed on the Indonesia Stock Exchange in 2015-2021. Sample determination in this study used purposive sampling. There are 7 companies that meet the criteria with a total of 49 data. The data analysis technique used in this study is multiple linear regressis analysis. The results of this study show that environmental performance measured using PROPER has no effect on Company Performance, Environmental costs have a negative and significant influence on Company Performance, Operating efficiency has no influence on the Company's Performance and Environmental performance, environmental costs and Operating efficiency together affect the Company's Performance in mining companies in 2015-2021